SLMP53-1 interacts with wild-type and mutant p53 DNA-binding domain and reactivates multiple hotspot mutations - Gomes, A. S. (2020)
Background Half of human cancers harbour TP53 mutations that render p53 inactive as a tumor suppressor. As such, reactivation of mutant (mut)p53 through restoration of wild-type (wt)-like function represents one of the most promising therapeutic strategies in cancer treatment. Recently, we have reported the (S)-tryptophanol-derived oxazoloisoindolinone SLMP53-1 as a new reactivator of wt and mutp53 R280K with in vitro and in vivo p53-dependent antitumor activity. The present work aimed a mechanistic elucidation of mutp53 reactivation by SLMP53-1. Methods and results By cellular thermal shift assay (CETSA), it is shown that SLMP53-1 induces wt and mutp53 R280K thermal stabilization, which is indicative of intermolecular interactions with these proteins. Accordingly, in silico studies of wt and mutp53 R280K DNA-binding domain with SLMP53-1 unveiled that the compound binds at the interface of the p53 homodimer with the DNA minor groove. Additionally, using yeast and p53-null tumor cells ectopically expressing distinct highly prevalent mutp53, the ability of SLMP53-1 to reactivate multiple mutp53 is evidenced. Conclusions SLMP53-1 is a p53-activating agent with the ability to directly target wt and a set of hotspot mutp53. General Significance This work reinforces the encouraging application of SLMP53-1 in the personalized treatment of cancer patients harboring distinct p53 status.